Basic physical meteorology textbook - Rybakova, Zh. V. (TSU Press, 2023)
This textbook includes the main sections of physical meteorology, which is a basic subject in the system of training specialists in the field of meteorology. The language of instruction is English. This makes it possible for students who do not speak Russian well enough, but speak English, to study the main concepts of physical meteorology. The textbook is for students of meteorology and students of related specialties.